National Identity and appreciation for sustainable practices in social and commercial entrepreneurs in Lima - Vera Ruiz, Angela (2022)
This comparative-correlational study aims to analyze and compare the relationship between appreciation for sustainable practices (APS) and national identity in two groups of social (n=135) and commercial (n=198) entrepreneurs in Lima-Peru. The results show that social entrepreneurs have higher APS and perceive Peruvians as warmer, more competent, and more moral than commercial entrepreneurs. Self-stereotype of competence and identification with the country explain APS significantly only significant in commercial entre-preneurs. The study analyzes little-explored psychosocial variables for the entrepreneurial phenomenon, proposing strategies to improve sustainability activities in entrepreneurs who do not have a explicit social orientation.